2020
DOI: 10.3390/biom10020278
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonate and Ethylene-Regulated Ethylene Response Factor 22 Promotes Lanolin-Induced Anthocyanin Biosynthesis in ‘Zaosu’ Pear (Pyrus bretschneideri Rehd.) Fruit

Abstract: Anthocyanin contributes to the coloration of pear fruit and enhances plant defenses. Members of the ethylene response factor (ERF) family play vital roles in hormone and stress signaling and are involved in anthocyanin biosynthesis. Here, PbERF22 was identified from the lanolin-induced red fruit of 'Zaosu' pear (Pyrus bretschneideri Rehd.) using a comparative transcriptome analysis. Its expression level was up-and down-regulated by methyl jasmonate and 1-methylcyclopropene plus lanolin treatments, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 67 publications
(76 reference statements)
0
17
0
Order By: Relevance
“…Our previous study indicated that lanolin promotes pear anthocyanin accumulation (Wu et al 2020). By further analyzing the transcriptomic data, we found that the expression levels of 61 WRKY TFs were upregulated after lanolin treatment (Tables S1 and S3).…”
Section: Pbwrky75 May Be Related To Pear Anthocyanin Synthesismentioning
confidence: 76%
“…Our previous study indicated that lanolin promotes pear anthocyanin accumulation (Wu et al 2020). By further analyzing the transcriptomic data, we found that the expression levels of 61 WRKY TFs were upregulated after lanolin treatment (Tables S1 and S3).…”
Section: Pbwrky75 May Be Related To Pear Anthocyanin Synthesismentioning
confidence: 76%
“…In fruit, some studies focused on the ERF genes related with fruit colour, texture, flavor and ripening by using transgenosis or RNAi mostly existing in model fruit Tomato LeERF1 was found to be associated with fruit ripening and softening (Li et al, 2007) and Le-ERF2 could trigger fruit ethylene synthesis (Zhang et al, 2009). PbERF22 in pears was found to respond to jasmonate, ethylene signals and affect fruit anthocyanin biosynthesis (Wu et al, 2020). ERF genes have not been widely studied in different fruit species for the lack of genomic information.…”
Section: Discussionmentioning
confidence: 99%
“…Phytohormones are indispensable for the processes of plant growth and development, and known plant hormones, such as JA (jasmonate), ABA (abscisic acid), ethylene and auxin, could stimulate the ethylene response factor family (ERF) and be involved in the regulation of anthocyanin biosynthesis [55][56][57]. In red pear and A. thaliana, JAZ (jasmonate ZIM-domain) proteins are substrates of the SCF COI1 complex, which interferes with the transcriptional levels of WD/bHLH/MYB complexes by interacting directly with the C-terminus of both bHLH and MYB members, in turn repressing anthocyanin biosynthesis [58].…”
Section: Phytohormonesmentioning
confidence: 99%